2014
DOI: 10.1097/mcc.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Neurocritical care

Abstract: Neurocritical care is an evolving field that is associated with improvements in outcomes over the past decade. Further research is required to determine how monitoring and treatment protocols can be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…1,2,27 However, like other studies that examine the impact of neurocritical care, the implementation of our service involved a number of changes, including cEEG, as well as education for bedside physicians and nurses, and seizure management guidelines; thus, a single causal explanation for reduced medication use cannot be definitively identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,27 However, like other studies that examine the impact of neurocritical care, the implementation of our service involved a number of changes, including cEEG, as well as education for bedside physicians and nurses, and seizure management guidelines; thus, a single causal explanation for reduced medication use cannot be definitively identified.…”
Section: Discussionmentioning
confidence: 99%
“…While there is strong evidence that adults with acute neurological conditions who are treated in a specialized neurocritical unit have reduced morbidity and mortality, 1,2 the impact of neurocritical care in the neonatal population is not known. Several reasons for improved outcomes have been proposed, including: (1) higher patient volumes in designated centers, (2) adherence to protocols, and (3) multimodal neurological monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a recent meta-analysis of more than 40,000 adult patients with brain injury concluded that patients treated in a neurocritical care unit had improved mortality as well as improved neurological outcomes. The authors of the study attributed improved patient care to the specific expertise gained from health care providers in repeatedly caring for this specific patient population, reduction of unnecessary practice variation with adherence to protocols, and multi-modal neuromonitoring (19). Much remains to be learned about specific implementation strategies and metrics utilized at such centers, and their link to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of predictors most influential in ICULOS may lead to earlier intervention and control of autonomic discharges. In turn, this might facilitate the earlier use of pharmacologic neuro-stimulation, rehabilitation and expedite discharge to high level brain injury recovery programs (Wheaton, Mathias, & Vink, 2009;Whyte et al, 2013) as specialized care by neurotrauma specialists in acute care and rehabilitation is known to improve hospital outcome and the likelihood of community re-integration following TBI (Haas et al, 2009;Kramer & Zygun, 2014;Whyte et al, 2013).…”
mentioning
confidence: 99%